Review Notes and Study Guide to the Republic and the Dialogues of Plato - Hagerty, Thomas ((Monarch Notes and Study Guide))
Breve comentario a quince diálogos de Platón: La República, Symposium, Gorgias, Protagoras, Euthyphro, Apology, Crito, Phaedo, Phaedrus, Ion, Theatetus, Meno, Menexenus, Timaeus, Philebus.